M Kualitas Laporan Keuangan: Penerapan Akuntansi Sektor Publik Terhadap Akuntabilitas Kinerja Instansi Pemerintah (Studi Kementerian Perhubungan BPTD Kelas II Provinsi Gorontalo) - Puyo, Marten (Kajian Ekonomi dan Bisnis, 2023)
Improving the quality of financial reports can be done by consistently applying public sector accounting standards and conducting regular audits of financial reports. The aim of the research is to determine and analyze the role of the quality of financial reports in moderating the application of public sector accounting reporting standards on the accountability of government agency performance. The research method approach used is a quantitative research method with the type of analysis used is survey analysis, using the PLS-SEM (partial least square modeling) analysis tool. The sample in the research was financial report managers, namely 46 respondents. Based on the results of this research, firstly, the implementation of public sector accounting has a positive and significant effect on the accountability of government agency performance. Second, the quality of financial reports cannot moderate the application of public sector accounting to the accountability of government agency performance. The higher the quality of the financial reports, the greater the possibility that the financial reports can meet the information needs of stakeholders